The canonical signs in the Quranic verses that indicate fanaticism and stubbornness - علي, عزيز سليم; حمزة, عباس يونس (Journal of College of Education, 2018)
This study deals with the art of Arabic rhetoric, which is the art of metaphor. The attention has been drawn to the study of this rhetorical art since the emergence of the Arabic rhetorical studies, and then to examine the implications of this rhetorical art in the Quranic verses that indicate intolerance and stubbornness. , And the technical expressions that dazzled the Arabs before the Ajam, and thus the Koran is the best and richest text to study all the arts of expression and eloquence, and research in the meanings of words and words need a great effort, and it is not hidden what the search in the Quranic verses of tools and possibilities, The sanctity of this text and the abundance of its meanings and pluralism, and suitability for every time and place .In this research, I have tried to mention a number of Qur'anic examples that we have seen bearing the significance of fanaticism and stubbornness, in which there is a hidden meaning in the meaning of the Qur'anic verse and in the books of Arab interpretations and eloquence, In the Koran, especially in the verses of intolerance and obstinacy go out to more than meaning and significance, and most of these meanings are the cynicism and ridicule of the fanatical supporters, and revealed what in their hearts of hatred and hatred towards Islam and Muslims, and other indications and meanings .This research has been divided into two parts: I spoke in the preface to intolerance and stubbornness in language and terminology in a concise manner, and in the terminology of the language and the term .